2022
DOI: 10.1161/strokeaha.121.036800
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Their Metabolites in Stroke: A Double-Edged Sword

Abstract: Besides damaging the brain, stroke causes systemic changes, including to the gastrointestinal system. A growing body of evidence supports the role of the gut and its microbiota in stroke, stroke prognosis, and recovery. The gut microbiota can increase the risk of a cerebrovascular event, playing a role in the onset of stroke. Conversely, stroke can induce dysbiosis of the gut microbiota and epithelial barrier integrity. This has been proposed as a contributor to systemic infections. In this review, we describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(121 citation statements)
references
References 116 publications
1
117
0
3
Order By: Relevance
“…Under physiological conditions, the intestinal microbiota of healthy adults is in dynamic balance almost all the time, with the most abundant microbiota being anaerobic bacteria and Clostridium perfringens (Tan et al, 2021;Chidambaram et al, 2022;Peh et al, 2022). In pathological conditions, however, the composition and diversity of the intestinal microbiota are altered.…”
Section: Changes In Gut Microbiota Composition and Diversity After Ismentioning
confidence: 99%
See 1 more Smart Citation
“…Under physiological conditions, the intestinal microbiota of healthy adults is in dynamic balance almost all the time, with the most abundant microbiota being anaerobic bacteria and Clostridium perfringens (Tan et al, 2021;Chidambaram et al, 2022;Peh et al, 2022). In pathological conditions, however, the composition and diversity of the intestinal microbiota are altered.…”
Section: Changes In Gut Microbiota Composition and Diversity After Ismentioning
confidence: 99%
“…Patients with IS often experience complications such as gastrointestinal bleeding, microbiota imbalance, and constipation, which accelerates disease progression and worsens prognosis (Benakis et al, 2016;Kapil et al, 2017;Chen et al, 2019c;Li et al, 2019;Fralick et al, 2020;Pluta et al, 2021). In recent years, researchers have amassed findings that strongly suggest a dynamic association between the gut-brain axis and IS; this topic may become a new research hotspot, which could expedite identification of potential therapeutic targets and eventually result in an intervention that could improve the prognosis of IS (Battaglini et al, 2020;Sinagra et al, 2021;Fang et al, 2022;Peh et al, 2022). 10.3389/fnins.2023.1081347 The gut possesses both digestive and immunomodulatory functions while also hosting a microbial ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it was recently reported that polyphenol enriched oat extracts increased the proliferation of beneficial gut microbiota, showing a positive correlation between antioxidant activity and prebiotic effect, which suggest that these polyphenols could be used to regulate the gut microbiota composition [ 131 ]. In this sense, certain changes in gut microbiota have been described to increase the risk of a cerebrovascular event, and, inversely, stroke can induce dysbiosis [ 133 ]. Therefore, a therapeutic effect of phenolic acids and flavonoids by the modulation of gut microbiota in experimental models is plausible and future studies targeting polyphenols–gut interplay are warranted.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Although Treg cells are closely related to neuroprotective function by inhibiting pathogenic T cells, some cytokines produced and secreted by they may associated with neurotoxicity ( 206 , 207 ). In addition, species diversity of intestinal microecology decreases after stroke ( 208 ). Specifically, alterations are observed within the highly abundant phyla Firmicutes, Bacteroidetes and Actinobacteria ( 209 ).…”
Section: The End Of the Bridge: Systemic Immune System Disordermentioning
confidence: 99%